Playing solo, against rivals, or in a team? Exploring individual, competitive, and cooperative dynamics in gamified digital education - Coelho, F.; Rando, B.; Bernardes, R.; Pontífice-Sousa, P.; Gonçalves, D.; Abreu, A. M. (Entertainment Computing, 2026)
While gamification is increasingly applied in education, research rarely compares distinct social dynamics and evaluates their cognitive, emotional, and motivational impact in a learning context. This study examines the effects of social gamification in education using a digital learning platform and a randomized controlled trial (RCT). Following research standards (CONSORT, Cochrane Collaboration, EVAT©), we compared individual, competitive, and cooperative gamification modes to assess the impact of social dynamics on nursing undergraduate students (n = 42). We analyzed participant characteristics (sociodemographics, gaming habits, player traits) alongside cognitive (learning, engagement, eye-tracking visual attention), emotional (facial emotion recognition), and motivational (intrinsic motivation) outcomes. Participants in the individual mode showed significantly higher eye-tracking visual attention than those in competition or cooperation modes. Social gamification appeared to reduce attention, likely due to cognitive overload from digital multitasking and distractions. Given the rise of the attention economy, individual gamified sessions may better sustain focus, aligning with trends toward personalized digital learning. Digital social gamification may not mirror the benefits of in-person interaction. The absence of significant differences in outcomes beyond visual attention may stem from contextual factors—such as weak social traits, low gaming interest, and health-related backgrounds—suggesting effective gamified strategies must align with learner profiles and context.